Livestock keepers’ perception of indigenous goat breeds and their contribution to livelihoods in Pakistan - Khan, M.S.; Muhammad, M.S.; Abdullah, M.; Hassan, F.; Waheed-uz-Zaman; Ashfaq, M.; Bett, R.C.; Baltenweck, Isabelle; Poole, Elizabeth J.; Ibrahim, Mohamed N.M.; Okeyo Mwai, Ally (2013)
The objective of this study was to determine the objectives of goat production, related management practices and their role in the live of rural poor through Participatory Rural Appraisal at two experimental sites including Bahawalpur (Site I) and Faisalabad (Site II) in Pakistan. Three villages were randomly selected from each site for appraisals. The data were collected through discussions with the livestock keepers about the goat production systems, contribution to livelihood, role in livelihood, breeding and selection, key constraints and sale of animals. The data were analysed using Chi square test. It was found that contribution of livestock to livelihood was significantly (P<0.05) differed between sites. Its contribution to livelihood and income of genders within Site I was significant (P<0.01). All other parameters were non-significant. Role of goats was also non-significant (P>0.05) between sites and between genders with the only exception for poor and all except very poor differences (P<0.001). Modes of spending money and trends were different between sites (P<0.001). The preferred traits were number of kids, feed intake and age at maturity in Teddy goats while milk yield, body size, colour, disease resistance and taste of meat in Beetal goats. Makhi Cheeni strain of Beetal goats is preferred at Site I and Black and White spotted strain of Beetal breed is preferred at Site II. Major constraints identified were problems in production and sales, disease attacks, mortality, scarcity of drinking water, predation, theft, lack of quality breeds, feed and finance. It is suggested that government should extend professional and financial services to minimize these constraints for the uplift of rural poor through goat production.